Investigation of β-Carboline Alkaloid Harmaline Against Cyvirus cyprinidallo3 Infection In Vitro and In Vivo - Clement Manes; Kristen Larson; Shelby Matsuoka; Xisheng Wang; Ruth Milston-Clements; Ling Jin (Viruses)
Cyvirus cyprinidallo3, also known as Cyprinid herpesvirus 3 (CyHV-3), is a common pathogen of koi and common carp (Cyprinus carpio). Infection of CyHV-3 can lead to high mortality in fry under 4 months of age. CyHV-3 can become latent in recovered fish, and latent CyHV-3 can reactivate under stress conditions and spread the virus. Reactivation of CyHV-3 can also lead to mortality and diseases in latently infected fish. No effective drugs are available to prevent CyHV-3 infection or reactivation from latency. There is a need for the discovery of anti-CyHV-3 drugs. Harmine (HAR) and harmaline (HAL) are β-carboline alkaloids found in the medicinal plant Peganum harmala with antiviral activities against many viruses, including HSV. Here, HAL was evaluated against CyHV-3 infection in vitro and in vivo, respectively. Immediately after a one-hour infection exposure of ~1000 FPU/plate or ~500 PFU/plate, cells treated with 5 µM HAL for 2 h can block nearly 50% or 90% plaque formation in vitro. Only around 50% inhibition was observed in cells treated with the common anti-herpesvirus drug acyclovir (ACV) at 10 or 20 µM for 2 h following 1 h post-infection of ~500 PFU/plate. Cells treated with 10 µM HAL for 30 min, 60 min, 2 h, and 6 h can reduce 60%, 65%, 85.5%, and 85% CyHV-3 replication in vitro, respectively. HAL at 20 µM is still effective against CyHV-3 DNA replication and virion production when the treatment started at 3 and 5 days post-infection for 1 or 2 h, respectively. HAL under 50 µM has little toxicity to cells treated for 24 h. Immersion treatment with 10 µM HAL for 3–4 h daily within the first 5 days post-infection can increase the survival of fry by 60%. In addition, IM injection of HAL at 20 µM can reduce the rate of CyHV-3 reactivation induced by heat stress in latently infected koi. This study demonstrated that HAL could potentially be used to prevent CyHV-3 infection or reactivation from latency.